Committed, Caring and Compassionate: Co. Kildare Workforce, Wellbeing, Attitudes towards Trauma-informed Care, COVID concerns and Ongoing Training Needs - Dobutowitsch, Mira (Kildare CYPSC, 2020)
This report details the results of a professional training needs analysis, which was undertaken by Kildare Children and Young People’s Services Committee (CYPSC), in collaboration with Maynooth University, Marino Institute of Education, and Kildare Youth Services, in response to a key priority in relation to workforce development as identified in Kildare CYPSC three-year Action Plan (2019-2021). The training needs analysis was targeted at all professionals working with children, young people and/or families in Co. Kildare. An online survey was designed and distributed to agencies and individuals across the county. In addition to exploring completed CPD and future training needs, the survey also included questions on COVID-19 challenges and training needs, as well as exploring professional wellbeing, self compassion and attitudes toward trauma-informed care. A total of 132 participants (79% female) completed the survey. Results showed key priorities for training in areas of trauma informed practice, cultural diversity, parenting support, mental health, and domestic violence. The study also found that Kildare professionals are faring well in terms of their own wellbeing, although the Covid-19 pandemic created new and diverse challenges. It highlights the diverse range of skills and expertise held by professionals in County Kildare. It also apparent that there is considerable interest in engaging in further CPD and that Kildare professionals endorse empathy-oriented and relationship-focused values and dispositions. A number of recommendations about ongoing work force development are provided.
Keywords: Trauma-informed practice; CPD; Continuous Professional Development; Cultural diversity; Parenting support; Mental Health; Domestic violence; Childhood trauma; Kildare; Ireland; Youth services; Covid-19; Sexuality; Relationships; Professional training